UR_GERICHTE 04/05 21 vom 27. April 2004 - UR Obergericht (2004)
Strassenverkehrsrecht. Art. 90 Ziff. 2 SVG. Art. 36 Abs. 1 VRV. | Strassenverkehrsrecht. Art. 90 Ziff. 2 SVG. Art. 36 Abs. 1 VRV. Rückwärtsfahren auf der Autobahn. Grobe Verkehrsregelverletzung.